A Comparison of Curricula of Graduate Schools of Interpretation and Translation in Korea - Lim, Hyang-Ok (Meta, 2006)
AbstractIn less than a decade, the number of graduate schools of interpretation and translation in Korea has skyrocketed from one to a dozen. This is a reflection of the increasing interest in practical studies across the board, but in interpretation, in particular.At such a juncture, it would be helpful to compare the entire process from entrance exams to curricula and finally the graduation exams to see whether the programs are the same or different and ultimately to proffer a “model” program that suits the current situation in Korea.Four graduate schools were chosen for this study: Hankuk University of Foreign Studies, the oldest graduate school of its kind in Korea, Ewha Womans University, Seoul University of Foreign Studies and Sunmoon University, as a local representative.